2013
DOI: 10.3201/eid1907.121365
|View full text |Cite
|
Sign up to set email alerts
|

Transmission ofStreptococcus equiSubspecieszooepidemicusInfection from Horses to Humans

Abstract: Streptococcus equi subspecies zooepidemicus (S. zooepidemicus) is a zoonotic pathogen for persons in contact with horses. In horses, S. zooepidemicus is an opportunistic pathogen, but human infections associated with S. zooepidemicus are often severe. Within 6 months in 2011, 3 unrelated cases of severe, disseminated S. zooepidemicus infection occurred in men working with horses in eastern Finland. To clarify the pathogen’s epidemiology, we describe the clinical features of the infection in 3 patients and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
6

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 36 publications
1
94
0
6
Order By: Relevance
“…The wide occurrence of these pathogens causing septic arthritis in horses can be justified by the presence of this group of microorganisms on the skin of animals, making it easy for traumatic inoculation into the articular region, contamination of intra-articular administration of drugs (iatrogenic route) (Steel et al 2013), or systemic dissemination from the upper respiratory tract (Songer & Post 2005, Orsini 2006). In addition, Pelkonen et al (2013) warned about the zoonotic potential of Streptococcus equi subsp. zooepidemicus in Finland as a causative agent of an emerging disease with severe evolution in humans, given the risk of transmission to humans that are in close contact with infected horses.…”
Section: Discussionmentioning
confidence: 99%
“…The wide occurrence of these pathogens causing septic arthritis in horses can be justified by the presence of this group of microorganisms on the skin of animals, making it easy for traumatic inoculation into the articular region, contamination of intra-articular administration of drugs (iatrogenic route) (Steel et al 2013), or systemic dissemination from the upper respiratory tract (Songer & Post 2005, Orsini 2006). In addition, Pelkonen et al (2013) warned about the zoonotic potential of Streptococcus equi subsp. zooepidemicus in Finland as a causative agent of an emerging disease with severe evolution in humans, given the risk of transmission to humans that are in close contact with infected horses.…”
Section: Discussionmentioning
confidence: 99%
“…S. zooepidemicus was also reported as an etiologic agent in canine infectious respiratory disease [10] and has also been reported to cause septicaemia, meningitis, nefritis and arthritis in humans [11][12][13][14] . Molecular typing methods showed that human and equine isolates were identical and closely related, according to these datas S. zooepidemicus should also be recognized as an emerging zoonosis [15] . S. equisimilis is considered to be an infrequent pathogenic agent isolated from horses.…”
Section: Introductionmentioning
confidence: 88%
“…Infectious respiratory disease of dogs [6], stranglers in horses [7], mastitis in goats [8], polyserositis in alpaca [9], rhinitis and meningitis of cats [10], septicemia, and wound infections in lambs, puppies, and greyhounds, septicemias in chickens and dolphins, lymphadenitis in guinea pigs [5], hemorrhagic pneumonia in broilers [11] are examples of its wide range of pathogenicity. Although S. zooepidemicus is an opportunistic pathogen for horses, infections in humans are often severe [12]. Human infections with S. zooepidemicus usually occur after consumption of unpasteurized products from goat and cow milk, pork meat or close contacts with horses and dogs [3,4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although S. zooepidemicus is an opportunistic pathogen for horses, infections in humans are often severe [12]. Human infections with S. zooepidemicus usually occur after consumption of unpasteurized products from goat and cow milk, pork meat or close contacts with horses and dogs [3,4,[12][13][14]. Clinical manifestations of human infections with S. zooepidemicus include pharyngitis, septicemia, meningitis, purulent arthritis and endocarditis [14].…”
Section: Introductionmentioning
confidence: 99%